1974
DOI: 10.3758/bf03333400
|View full text |Cite
|
Sign up to set email alerts
|

The reported sleep characteristics of meditators and nonmeditators

Abstract: A sleep questionnaire was administered to a group of experienced meditators and to an appropriate control group. Meditators reported that they awakened in the morning more rested than nonmeditators. :\1editators also reported more dreaming and a more positive quality in their dream content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1977
1977
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…First, getting inspirations from dreams is-of course-closely related to dream recall frequency, as has been demonstrated for creative insights stimulated by dreams (Schredl & Erlacher, 2007). Second, spiritual practices like meditation and related techniques of contemplation like Autogenic Training are correlated with an increased dream recall frequency (Albert & McNeece, 1974;Busby & De Koninck, 1980;Reed, 1976Reed, , 1978Schredl & Doll, 1997). As undergoing psychotherapy also increases dream recall (Myers & Solomon, 1989;Schredl, Bohusch, Kahl, Mader, & Somesan, 2000), this variable was also included in the analysis.…”
mentioning
confidence: 99%
“…First, getting inspirations from dreams is-of course-closely related to dream recall frequency, as has been demonstrated for creative insights stimulated by dreams (Schredl & Erlacher, 2007). Second, spiritual practices like meditation and related techniques of contemplation like Autogenic Training are correlated with an increased dream recall frequency (Albert & McNeece, 1974;Busby & De Koninck, 1980;Reed, 1976Reed, , 1978Schredl & Doll, 1997). As undergoing psychotherapy also increases dream recall (Myers & Solomon, 1989;Schredl, Bohusch, Kahl, Mader, & Somesan, 2000), this variable was also included in the analysis.…”
mentioning
confidence: 99%
“…Accordingly, functions of heartbeat, sweating, breathing, and digestion are controlled by the ANS. Recent studies highlighted the psycho-physiological aspects of meditation and its effect [5][6][7][8][9][10][11][12][13][14][15].…”
Section: Abstract -2d and 3d Poincaré Plot 3d Frequency Delay Plot mentioning
confidence: 99%
“…Accordingly, functions of heartbeat, sweating, breathing, and digestion are controlled by the ANS. Recent studies highlighted the psycho-physiological aspects of meditation and its effect [5][6][7][8][9][10][11][12][13][14][15].Typically, the HRV is a popular non-invasive tool to assess different conditions of heart [16][17][18][19]. Nowadays, it is observed that HRV reflects some psychological conditions [20,21].…”
mentioning
confidence: 99%